Defect-rich spinel ferrites with improved charge collection properties for efficient solar water splitting - Tan, Runfa; Jeong, Yoo Jae; Li, Qu; Kang, Minje; Cho, In Sun (Journal of Advanced Ceramics, 2023)
Spinel zinc ferrite (ZnFe2O4, ZFO) is a potential photoanode material for photoelectrochemical (PEC) water splitting because of its ideal bandgap (1.9–2.1 eV) and superior chemical stability in aqueous solutions. However, the low charge collection efficiency significantly hinders the improvement in PEC activity. Herein, we report an ultrafast and effective flame activation route to enhance the charge collection properties of ZFO. First, high-temperature flame (> 1300 ℃) facilitated surface and grain boundary diffusions, increasing the grain size and connectivity of the ZFO nanoparticles. Second, the reducing atmosphere of the flame enabled the formation of surface defects (oxygen vacancy and Fe2+), thereby increasing the charge carrier density and surface adsorption sites. Significantly, these two factors promoted charge transport and transfer kinetics, resulting in a 10-fold increase in the photocurrent density over the unactivated ZFO. Furthermore, we deposited a thin Al2 O3 overlayer to passivate the ZFO surface and then the NiFeOx oxygen evolution catalyst (OEC) to expedite hole injection into the electrolyte. This surface passivation and OEC deposition led to a remarkable photocurrent density of ~1 mA/cm2 at 1.23 V versus the reversible hydrogen electrode, which is the highest value among all reported ZFO photoanodes. Notably, the NiFeOx/Al2 O3 /F-ZFO photoanode achieved excellent photocurrent stability over 55 h (96% retention) and superior faradaic efficiency (FE > 94%). Our flame activation method is also effective in improving the photocurrent densities of other spinel ferrites: CuFe2 O4 (93 times), MgFe2 O4 (16 times), and NiFe2 O4 (12 times).
Keywords: Charge collection; Charge collection properties; Defect-rich surface; Flame activation; Oxygen evolution; Photocurrent density; Photoelectrochemical; Photoelectrochemicals; Spinel ferrites; Water splitting; charge collection; defect-rich surface; flame activation; photoelectrochemical (PEC); spinel ferrites; water splitting